Nocturnal mother–juvenile offspring interaction at the beginning of the juvenile period in free-ranging spider monkeys (Ateles geoffroyi): a report on two cases. Issue 4 (3rd July 2020) - Hidalgo-Aguirre, Rosa M.; Cruz-Aguilar, Manuel A.; Hernández-González, Marisela; Guevara, Miguel A.; Rovirosa-Hernández, Ma. de Jesús
Abstract : The objective of this study was to describe the nocturnal behavior patterns of the interaction between mothers and their juvenile offspring at the beginning of the juvenile period in two dyads of free-ranging spider monkeys ( Ateles geoffroyi ). Based on direct field observation, we recorded six interaction behaviors between mothers and their juvenile offspring at nighttime and during the daylight period. The frequencies and proportions of each behavior recorded were analyzed for both conditions, and qualitative descriptions of each behavior were made. Observations revealed that the percentage of proximity in the dyads tended to increase at nighttime compared to the daylight period. In one of the dyads, we observed that the percentage of grooming also showed an upward tendency at nighttime compared to the daylight period. The dyads remained together to sleep during all 8 days of the study and were seen to seek arm-in-arm contact and to perform grooming behaviors. Our results suggest that mother–juvenile interaction at the onset of the juvenile period in spider monkeys may be characterized by greater proximity and social grooming behaviors, while the nocturnal observations suggest a strong attachment between mothers and their juveniles in this stage.